Assessing the relationship between program education objectives and program learning outcomes in outcome-based education using partial least squares-structural equation model - Zulkifley Mohamed (Tanjong Malim, 2019)
Assessing the relationship between program education objectives and program learning outcomes in outcome-based education using partial least squares-structural equation model by Zulkifley Mohamed